A subversão do gênero em Leopardso de Kafka - Lucas, Jeane (2010)
Literary production of the nineties and the early years of the twenty-first century is characterized the release of some literary genres, specifically what Literary Theory defined as being a novel, which do not fit the standards of Classical Literature or the peculiarities of the so-called Best Sellers. Therefore, this thesis has as its object of study the book Leopardos de Kafka, by Moacyr Scliar, which is part of the collection of detective novels Literature and Death, released by the publisher Companhia das Letras. This study aims to show the narrative resources and how they were used in the novel aforementioned, so that we can show that they break the existing boundaries between Classical Literature and Best Sellers and the standards of the traditional detective novel. For this objective to be achieved, the theoretical foundation of this thesis was based, mainly, on studies of the detective novel, done by Boileau and Narcejac (1991), Albuquerque (1979), Reimão (1983, 2005) and others; in researches on Best Sellers, done by Sodré (1978), Caldas (2000) among others and on studies of Historiographic Metafiction, postmodernism and narcissistic narrative, made by Hutcheon (1984, 2002).